Limits of classical world with finite information - Ganardi, Ray Fellix (2015)
Computer simulations are getting more and more common in physics. Here we examine the underlying assumption that Nature can be simulated with classical bits. We first postulate that every physical object can be encoded into a finite number of classical bits. We allow the bits to have an unknown but fixed probability distribution. The second postulate is that measurements can be computed as deterministic functions on these bits. It is shown that we can model exponentially many measurements with n bits. We also derive the minimum precision that one needs in order to disprove this model in an experiment. Finally, imposing quantum mechanical restrictions on measurement devices we show that disproving the classical models with only about 100 bits is already practically impossible.